In silico ADMET prediction, evaluation of cytotoxicity in mouse splenocytes and preliminary evaluation of in vitro antimalarial activity of 4-(4-chlorophenyl)thiazole compounds - Silva, Beatriz R.M.G.DA (2023)
In this work, an in silico study and evaluation of the cytotoxicity of 4-(4-chlorophenyl)thiazole compounds against mouse splenocytes and the chloroquine-sensitive Plasmodium falciparum 3D7 strain are reported. The in silico results showed that the compounds have important pharmacokinetic properties for compounds with potential drug candidates. Regarding cytotoxicity assays against splenocytes, the compounds have low cytotoxicity. In addition, they were able to promote activation of these cells by increasing nitric oxide production without promoting cell death. Finally, they were able to promote cell proliferation. Regarding the in vitro anti-P. falciparum activity assays, it was observed that the compounds were able to inhibit the parasite's growth, presenting IC50 values ​​ranging from 0.79 to greater than 10 µM. These results are promising when compared to chloroquine. Therefore, this study showed that 4-(4-chlorophenyl)thiazole compounds are promising candidates for antimalarials.